Analysis of 'Beauty Bestie' Perceptions Built in Emina Beauty Bestie Day Campaign - Nyoman Indy Tavipiana Wirata; Rah Utami Nugrahani (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Beauty has become a hot topic in public discussions, especially adolescent girls with various definitions of 'beautiful' that exist. However, the influence of technology has created specific beauty standards. In the transition process, adolescents begin to realize the importance of physical appearance to affect their self-confidence. This study analyzes the perception of 'Beauty Bestie' built in the Emina Beauty Bestie Day campaign by Emina Cosmetics as a support system for teenagers to overcome their skin problems, so that the object in this study is the perception of 'Beauty Bestie' and the subjects are campaign audiences as key informants and psychology experts as expert informants. This study used interpretive qualitative research methods with a phenomenological approach and research data obtained through in-depth interviews, observation, and documentation. Social cognitive theory was used as a foundation for reviewing this research and Van Kaam's phenomenological data analysis techniques were used to analyze data findings with data analysis units oriented to the stage of perception formation by Julia T. Wood and DeVito. The results showed that the perception of 'Beauty Bestie' built in the Emina Beauty Bestie Day campaign has been formed in the campaign audience to the stage of recall. This research is only limited to the formation of the perception of 'Beauty Bestie' in the Emina Beauty Bestie Day campaign, so that future research can further analyze the perception of 'Beauty Bestie' in the campaign audience in terms of brand positioning, brand image, or sales. Keywords: Beauty Standards; Formation of perception; Beauty Bestie; Campaign